Artistic Design as a Sign System: A Semiotic Study of Roland Barthes in the Film “Sinners (2025)” (Universitas Pendidikan Indonesia, 2025)
This study analyzes the artistic design in the film Sinners (2025) using Roland Barthes’ semiotic approach to uncover the meanings behind its visual elements. The primary focus is directed toward props and symbols such as the guitar, cutting wounds, and the cross, which function not merely as aesthetic complements but also as sign systems conveying profound messages related to identity, trauma, and ideology. Through the stages of denotation, connotation, and myth analysis, this study finds that the artistic design in the film represents complex social and cultural narratives, such as inherited sin, collective suffering, and the characters’ existential struggles. These symbols construct discourses on morality, religiosity, and internal conflict, positioning the artistic design as a medium of ideological expression that reinforces the film’s overall narrative meaning.